Your cheating heart is just afraid of ending up alone: Fear of being single mediates the relationship between attachment anxiety and infidelity. (1st January 2021) - Sakman, Ezgi; Urganci, Betul; Sevi, Barış
Abstract: Despite their detrimental effects, acts of infidelity are common. Several individual differences, including attachment orientations, have been linked to infidelity behaviors. Yet, the mechanisms underlying the relationship between attachment anxiety and infidelity are not well understood. This deserves attention, as the positive association between chronic worry about being abandoned and engaging in infidelity, which inherently increases the risk of being left by the partner, poses a paradox. Studying an online community sample ( N = 233, 52.8% female, M age = 36.73, Rangeage = 20–70) using self-report measures, we aim to offer an explanation to this conundrum by hypothesizing that the relationship between attachment anxiety and infidelity behaviors is mediated by fear of being single (i.e., the concern about being left without a partner). We found that those who have greater attachment anxiety showed increased fear of being single, which in turn predicted greater infidelity behaviors. The associations held after controlling for sex, age, and relationship length. Results suggest that people high on attachment anxiety are more likely to be involved in extradyadic relationships due to their high fear of being single, possibly as a bet-hedging strategy to minimize future risk of being single. Findings are discussed vis-à-vis implications for couples counseling.